Communicating Eco-Islam: From Religious Values to Environmental Practices in a Disaster-Affected Community - Azwar, Muhammad; Sikumbang, Ahmad Tamrin; Ritonga, Elfi Yanti (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The growing frequency of environmental disasters and ecological degradation highlights the need for environmental approaches that integrate ecological responsibility with religious and ethical values. Previous studies have extensively examined tauhid (divine oneness), khalifah (stewardship), and mizan (balance) as normative foundations of Islamic environmental ethics. However, limited empirical research has examined how these established ecological values are communicated, interpreted, and connected to environmental practices within disaster-affected communities. Addressing this gap, this study examines how Islamic communication mediates the connection between Islamic ecological values and community environmental practices in Aceh Tamiang, Aceh. Using a qualitative field research design, data were collected through semi-structured interviews, observation, and documentation involving two purposively selected informants: Nasrullah Abdul Rahim, a humanitarian and environmental activist, and Naad Darul, a community member affected by floods and landslides. Data were analyzed thematically and validated through source and technique triangulation. The findings indicate that Islamic communication functions as a meaning-making mechanism through which tauhid, khalifah, and mizan are connected to community experiences of environmental disasters and ecological responsibility. Communication principles of tabligh (conveying the message), hikmah (wisdom), and uswah hasanah (exemplary conduct) facilitate this process through humanitarian activities, environmental initiatives, education, and community engagement. However, the findings also reveal that increased ecological awareness does not automatically translate into sustained environmental practices, as behavioral responses remain influenced by social conditions, economic circumstances, available facilities, and community support. This study contributes empirically to Islamic and environmental communication scholarship by demonstrating how religious ecological values are communicated and interpreted within a disaster-affected community, positioning Islamic communication as a bridge between religious meaning, ecological awareness, and environmental engagement rather than as a direct determinant of behavioral change.